Research on the selection of grid data storage technology - Chengling LI; Yuxiang ZHENG; Yiqi HONG; Wen LI; Huimin GUO (Dianxin kexue, 2018)
Unstructured data and real-time data were storaged by state grid company’s big data platform distributed file system (based on HDFS optimized package).Based on HDFS optimized packaging,HDFS was characterized by high fault tolerance,low cost and high throughput.It was suitable for large-scale data set applications and effectively supports large file storage.The unstructured data storage and real-time data storage was introduced,and the selection of grid data storage technology was studied.